ARTIFICIAL INTELLIGENCE AS A TOOL FOR FORMING INTEREST IN MATHEMATICS AMONG STUDENTS WITH LOW MOTIVATION TO LEARN - Y.S. Karyakin (Theoretical Hypotheses and Empirical Results, 2025)
This article explores the possibilities of applying artificial intelligence (AI) technologies to increase interest in mathematics among students with low learning motivation. The author analyzes the limitations of traditional teaching methods and proposes alternative approaches based on personalized learning, visualization of abstract concepts, interactive communication, and instant feedback. Examples of AI tools are provided, a model of the teaching methodology is described, and directions for further research are outlined. The work is practical in nature and may be useful to teachers, methodologists, and developers of digital educational solutions